Assessment of programmed death‐ligand 1 expression and tumor‐associated immune cells in pediatric cancer tissues. Issue 19 (13th June 2017) - Majzner, Robbie G.; Simon, Jason S.; Grosso, Joseph F.; Martinez, Daniel; Pawel, Bruce R.; Santi, Mariarita; Merchant, Melinda S.; Geoerger, Birgit; Hezam, Imene; Marty, Virginie; Vielh, Phillippe; Daugaard, Mads; et al.
Abstract : BACKGROUND: Programmed death 1 (PD‐1) signaling in the tumor microenvironment dampens immune responses to cancer, and blocking this axis induces antitumor effects in several malignancies. Clinical studies of PD‐1 blockade are only now being initiated in pediatric patients, and little is known regarding programmed death‐ligand 1 (PD‐L1) expression in common childhood cancers. The authors characterized PD‐L1 expression and tumor‐associated immune cells (TAICs) (lymphocytes and macrophages) in common pediatric cancers. METHODS: Whole slide sections and tissue microarrays were evaluated by immunohistochemistry for PD‐L1 expression and for the presence of TAICs. TAICs were also screened for PD‐L1 expression. RESULTS: Thirty‐nine of 451 evaluable tumors (9%) expressed PD‐L1 in at least 1% of tumor cells. The highest frequency histotypes comprised Burkitt lymphoma (80%; 8 of 10 tumors), glioblastoma multiforme (36%; 5 of 14 tumors), and neuroblastoma (14%; 17 of 118 tumors). PD‐L1 staining was associated with inferior survival among patients with neuroblastoma ( P  = .004). Seventy‐four percent of tumors contained lymphocytes and/or macrophages. Macrophages were significantly more likely to be identified in PD‐L1–positive versus PD‐L1–negative tumors ( P  < .001). CONCLUSIONS: A subset of diagnostic pediatric cancers exhibit PD‐L1 expression, whereas a much larger fraction demonstrates infiltration with tumor‐associated lymphocytes. PD‐L1 expression may be a biomarker for poor outcome in neuroblastoma. Further preclinical and clinical investigation will define the predictive nature of PD‐L1 expression in childhood cancers both at diagnosis and after exposure to chemoradiotherapy. Cancer 2017;123:3807–3815. © 2017 American Cancer Society Abstract : This is the first study to systematically interrogate programmed death‐ligand 1 expression in a large series of pediatric cancers. A high frequency of the ligand's expression is observed in pediatric patients with Burkitt lymphoma, glioblastoma multiforme, and neuroblastoma, and the identification of such expression at diagnosis is associated with inferior survival.